Oral Hygiene in Patients with Fixed Partial Dentures - A.Alagu Rathi Bharathi1 , M.SivaKumar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Fixed prosthodontics is the area of prosthodontics focused on permanently attached dental prosthesis. Patientswith FPD require regular lifelong professional maintenance with repeated interventions and reinstructionsregarding maintenance of proper oral hygiene around fixed prosthesis. The aim of the study is to evaluatethe oral hygiene in patients with Fixed Dental Prosthesis. A total 86000 patients data were analysed and thesamples were taken from the patients who checked into the hospital from June 2019 to April 2020. A totalof 958 patients were taken and analysed for oral hygiene status. Data collection was done from the dentalarchives of the patient management software system patented by Saveetha dental college.The data wasobtained from the category fixed dental prosthesis. The results were analysed using SPSS software version20 by IBM. The results observed was that the patients with FPD were prevalent to gingival inflammationand periodontal problems. Noticeable lack of awareness about oral hygiene after the fixed partial denture isfound among patients wearing Fixed Partial Denture.